DON’T WORRY ABOUT FORMALITIES: PROMPTING AS ALGORITHMIC FOLKLORE - Gunderson, Marianne (AoIR Selected Papers of Internet Research, 2026)
As large language models (LLMs) with chat interfaces such as ChatGPT have become available to the public, with ChatGPT reportedly amassing more than 400 million active users worldwide, social media has become host to a proliferation of posts and dedicated communities featuring lay people’s experiments with prompt engineering. While much has been written about prompting as a specialized skill, there is currently very little research on the socio-cultural practices of prompting and the online communities dedicated to these activities and little is known about how non-experts are using prompts to shape their interactions with LLMs. With this conference paper I aim to contribute to the understanding of LLM prompting as a vernacular practice in digital culture. Combining the method of digital ethnography of the proliferation and modification of a prompt known as "the eigenprompt" on the social media platform X.com, this paper explores how the how assumptions and ideals about LLM intelligence, interiority, and emotion are expressed through the practice of prompting, and how ideals and preferences about LLMs are negotiated and iteratively reformulated throughout online communities. Finally, I argue that the eigenprompt and similar vernacular prompts should be seen as examples of algorithmic folklore that contribute to the construction of new ways of being and relating to digital others.